Using cooperative game theory to determine profit distribution in IPD projects - Teng, Y.; Li, X.; Wu, Peng; Wang, X. (Taylor & Francis, 2017)
IPD (Integrated Project Delivery) mode is regarded as an effective project delivery method that could achieve the consensus project goals by a collaborative team. However, the number of projects using IPD remains small, partly because of the lack of a fair incentive scheme. The purpose of this paper is to develop a fair profit distribution scheme among stakeholders of IPD projects. This study uses cooperative game theory as the method for analyzing profit distribution among the designer, construction contractor, owner and BIM consultant. The Shapley value is used as the solution to the cooperative game theory because it can assess the marginal contribution of each stakeholder to the coalition. In addition, fuzzy comprehensive evaluation (FCE) and analytic hierarchy process (AHP) are used to assess the risk levels of each stakeholder to modify the profit distribution based on the marginal contribution. A modified Shapley value model, which includes four categories of risk factors, i.e. operation, economic, profit and market risks, was established in this study. The results show that the modified Shapley value can help establish a fair profit distribution scheme for the IPD projects. Practitioners are also encouraged to focus on information sharing to reach the full potential of IPD.